PTU-171 Calibration test findings of the new verify sns test stimulator. (22nd June 2015) - Etherson, KJ; Davidson, A; Close, H; Yiannakou, Y; Mason, JM
Abstract : Introduction: Sacral nerve stimulation (SNS) can be an effective treatment for some patients with functional bowel disorders. The highly variable nerve stimulation waveforms generated by the re-usable "brown box" (model 3625, Medtronic US) SNS test stimulator have previously been reported. 1 Since 2013, the single-use digital test stimulator "Verify" (model 3531, Medtronic US) has been used in our trust. Within the UK most clinicians continue to use the brown box; Medtronic no longer manufacture model 3625 and it requires recalibration between patient use. We aimed to assess the Verify stimulator's output waveform to quantify if this was as variable as the analogue precursor. Method: A prospective output waveform assessment of 15 used Verify SNS test stimulators using a cross-calibrated oscilloscope (Tektronix model 2230) and a counter-timer (Black Star Apollo 100). Devices were successively loaded with the same AAAA batteries and connected to a constant simulated tissue load (993Ω) circuit with two output electrodes attached to the oscilloscope (Figure 1) . The output waveform amplitude and pulse width were measured at clinically used settings and compared with the expected output values (amplitude by V = IR). Devices passed the calibration test if within tolerances of 10% and 20%. Results: At clinical settings (14 Hz/210 µSec) the measured amplitude and pulse width did not vary significantly from expected at a programmed current of 0.2, 0.5, 1.0, 2.0 and 3.0 mAmp, and 100% of devices passed the calibration test (Table 1 ). 6 devices failed at 0.1milliAmps due to more variation at low energy settings. The variations in device frequency were too small to be measured with the counter-timer and therefore in the order of magnitude of × 10 –4 Hertz. Similarly, the pulse width times were just as accurate at 100, 210 and 400 µSec with the standard deviations 0.48, 0.93 and 0.69 µSec respectively. Conclusion: At all clinically relevant settings 100% of the devices passed the calibration test. The failures at 0.1 mAmps are irrelevant (below therapeutic thresholds). Given these results, the lack of manufacturer support for the 3625 model, and its reported variability, we conclude that only the Verify testing device is fit for purpose in clinical practice. Disclosure of interest: None Declared. Reference: Etherson KJ, Davidson A, Yiannakou Y, Mason JM. Surgeons don't forget to calibrate: Findings from SNS test stimulators. Gut 2013;62 :A27-A8